Research Output of the Canadian Pharmaceutical Industry: Where Has All the R&D Gone? - Norman Kalant and Ian Shrier (Healthcare Policy, 2006)
Although the Canadian pharmaceutical industry claims to be spending about $1 billion per year for research and development (R&D), there is little evidence of research performed, as measured by scientific publications and patent applications. One firm was exceptional; it compared favourably with its parent firm in regard to the number of publications and patents in relation to the R&D budget, demonstrating the feasibility of developing a productive and independent research program in Canada. The perception of low productivity is made worse by the inadequacy of the annual report on R&D prepared by the Patented Medicines Prices Review Board (PMPRB). We recommend a number of changes in the PMPRB's mandate so that its collection of R&D data and subsequent analysis will be more complete. Further financial assistance to the industry should be withheld until accountability is assured and a full assessment of the outcome of its R&D program can be made. [To view the French abstract, please scroll down.]